Penganggaran Berbasis Kinerja: Antara Indonesia dan Korea Selatan - Irwan Suliantoro (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2023)
The implementation of Performance Based Budgeting (PBB) in Indonesia has not been directly integrated into the planning and budgeting process. In order to obtain a more comprehensive description, a study is needed regarding the implementation of PBB in South Korea. The South Korea was chosen as a comparison because it has a high-Performance Budgeting Index. The aims of this research are: 1) To analyze the strengths and the weaknesses of PBB implementation in Indonesia and South Korea; 2) Providing alternative policies related to the implementation of PBB in Indonesia to be more constructive. The research method was carried out through a descriptive qualitative approach. The results of the study show that the main advantage of PBB implementation in South Korea is the relationship between performance evaluation and budget allocation, but the weakness is that the review process is relatively long. The main advantage of PBB implementation in Indonesia is that there is a cost implementation standard at the initial stage of its implementation, but the weakness is that the performance evaluation results have not been integrated into the budget preparation process. Recommendations that need to be considered, namely the need for synchronization between the data from the results of the performance evaluation with the data needed at the time of preparing the budget. Further research is needed to formulate and describe how the format/layout of the data resulting from the performance evaluation can be in sync with the data in the budget preparation document.